Effects of the epiphytic patterns on endophytes and metabolites of Dendrobium nobile Lindl - Yu, Chengxin; Wang, Peng; Ding, Haiyan; Hu, Yuan; Wang, Fu; Chen, Hongping; Chen, Lin; Liu, Youping (Frontiers in Plant Science, 2024)
Dendrobium is an epiphytic herb plant with neuroprotective, gastroprotective, anti-inflammatory, and immunomodulatory effects. It's often found attached to tree trunks or rocks. With the development of the dendrobium industry, numerous epiphytic patterns exist, such as crushed stone, stump, sawdust, etc. The study of metabolites and endophytes of D. nobile under different epiphytic patterns, which revealed the effects of epiphytic patterns on D. nobile from the perspectives of metabolomics and microbiology, is of great significance for the healthy development of D. nobile. In the study, the D. nobile under five epiphytic patterns grown in the same environment were selected. The metabolites were investigated by widely targeted metabolomics, and the endophytes were sequenced using highthroughput sequencing methods. Then, a correlation analysis between the different metabolites and endophytes was performed. A total of 1,032 metabolites were annotated in D. nobile. There are more flavonoids and phenolic acids accumulated on the epiphytic pattern of Danxia stone, while the accumulation of lipids on the other epiphytic patterns, and 16 differential metabolites were screened out. The endophyte composition of D. nobile was dominated by Proteobacteria, Actinomycetes, unidentified bacteria, Firmicutes, and Cyanobacteria. For endophytic fungi, Basidiomycota and Ascomycota were the dominant phyla of D. nobile. The relative abundance of Spirosoma, Nocardioides, and Arrhenia in the Danxia stone was significantly higher than other epiphytic patterns.According to correlation analysis, we found a significant correlation between differential metabolites and Spirosoma, Nocardioides, and Arrheni. This study confirmed that Dendrobium quality was affected by its epiphytic patterns and revealed its possible causes from a microbiological point of view.